RE-VACCINATION OF CHILDREN OVER 1,5 YEARS OLD AGAINST DIPHTHERIA, PERTUSSIS, TETANUS, POLIOMYELITIS AND HEMOPHILIC INFECTION - S.M. Kharit; T.V. Chernyaeva; E.P. Nacharova; G.A. Vasil'eva; A.A. Ruleva ("Paediatrician" Publishers LLC, 2009)
The article presents the results of the observation of 200 children under the age 18-42 months (64 healthy children and 136 patients with allergic symptoms, residual lesions of CNS, frequently ailing children, and having reactions of previous vaccination in medical history) who were re-vaccinated with vaccine Pentaxim. It was shown that 77% of children had asymptomatic post-vaccinal period. Only 1,5% of patients showed severe reactions with fever > 38,6_С. Local reactions (not over 3-5 cm) developed in 25,5% of children with allergy, lesions of CNS and frequently ailing children, their rate was significantly higher than in healthy children (7,8%). No one had post-vaccinal complications. An estimation of reactogenicity of vaccine proved its safety and suitability of administration as first re-vaccination against pertussis, diphtheria, tetanus, poliomyelitis and one-time vaccination against Haemophilus influenzae type b in children after 1 year old in different state of health. Key words: children, vaccinations, Pentaxim, post-vaccinal period, safety. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):20-25)